Exploring the Relationship Between Mathematics Performance and Learn-ing Style Among Grade 8 Students - Ocampo, Evelina N.; Mobo, Froilan D.; Cutillas, Anesito L. (Future Science / FSH-PH Publications, 2023)
This study explored the relationship between mathematics performance and learning styles among Grade 8 students in the Philippines. The study used a descriptive correlation research design to achieve its objectives, which included determining the profile of Grade 8 students, identifying their learning styles, and examining the relationship between mathematics performance and age, gender, and learning styles. The data was collected through an adapted questionnaire from David Kolb's learning style inventory. The findings revealed no significant relationship between learning styles and academic performance in mathematics. However, it is worth noting that the lack of a significant relationship does not necessarily mean that there is no relationship at all. Motivation, teacher quality, and cultural background may also influence mathematics performance. The findings suggest that educators should consider students' different learning styles when developing effective teaching strategies to enhance mathematics performance among Grade 8 students. This study contributes to the literature on mathematics education and has practical implications for educators seeking to enhance their students' mathematics performance.